The Role of Local Government Councils in Emancipating Special Interest Groups: A Case Study of PWDs in Bukimbiri Sub-County Kisoro District. - Kamusiime, Daniel (Kabale University, 2023)
The study examined the role of local government councils in emancipating special interest groups. A case study of PWDs in Bukimbiri Sub County Kisoro district. It concentrated on the following research objectives; to examine the role of local government councils in emancipating special interest groups, to establish the challenges facing people with disability, and to establish measures taken by the government towards empowerment of people with disability. The study used a cross-sectional research design. According to Sarantakos (2005), cross-sectional research is designed by taking a cross-section of it at one time. This enabled the researcher to obtain a 'snapshot' of the outcome and the characteristics associated with the population under study, at a specific point in time. The study population consisted of 120 participants including; 50 Persons with Disabilities, 02 sub-county councilors for PWDs, 50 community members in the Bukimbiri sub-county, 10 service providers in the Bukimbiri sub-county, 03 Sub-county technical teams and 05 Non-disabled councilors in Bukimbiri sub-county. The researcher determined the sample size using the Krejicie and Morgan Table. This means that a population of 190 was represented by a sample size of 127 respondents. The study used both probabilistic and non-probabilistic sampling techniques. Data Collection Methods included a questionnaire method, interview method, and document review. The researcher used both quantitative and qualitative approaches to analyze the data which enabled the researcher to obtain relevant data for the study.